Pricing aspects in intellectual property agreements : A systematic literature review - Pilecká, Anežka (2025)
Franchising is a popular method for businesses to expand across different industries. However, setting prices in franchise agreements can be complex and is often debated. Fees and royalties are crucial as they help ensure the business system is profitable and that everyone involved stays motivated. Understanding how these prices are determined is important for franchise owners, operators, and researchers. Despite its importance, research on this topic is fragmented, making it hard to fully understand how pricing in franchising works. This thesis conducts a systematic literature review (SLR) to analyse and integrate findings. A careful selection process was used, resulting in a strong analysis. The study included 8 theoretical studies and 25 empirical studies, examining key pricing issues and broader trends in franchising. The research identifies 6 key aspects that influence pricing. (1) relationship between franchise fees and royalty rates, (2) brand value, (3) risk, (4) moral hazard, (5) monitoring, (6) support. In summary, this review organizes existing knowledge and connects theoretical concepts with practical applications. It emphasizes that franchise pricing needs to be flexible and adaptable to specific situations to foster successful and sustainable partnerships.